Historiografi haji Indonesia - Putuhena, M. Shaleh, 1938- (Yogyakarta : LKiS, 2007)
Dutch East Indies policy regarding Indonesian Muslim pilgrimages to Mecca ; history
Revision of the author's thesis (doctoral)--IAIN Sunan Kalijaga, Yogyakarta
Keywords: Muslim pilgrims and pilgrimages -- Indonesia -- History; Muslim pilgrims and pilgrimages -- Saudi Arabia -- Mecca